2021
DOI: 10.1016/j.celrep.2021.109343
|View full text |Cite
|
Sign up to set email alerts
|

Feedback control of PLK1 by Apolo1 ensures accurate chromosome segregation

Abstract: SUMMARY Stable transmission of genetic material during cell division requires accurate chromosome segregation. PLK1 dynamics at kinetochores control establishment of correct kinetochore-microtubule attachments and subsequent silencing of the spindle checkpoint. However, the regulatory mechanism responsible for PLK1 activity in prometaphase has not yet been affirmatively identified. Here we identify Apolo1, which tunes PLK1 activity for accurate kinetochore-microtubule attachments. Apolo1 localizes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Alike other scaffolding proteins such as REV7, it is possible that C1orf112 forms different molecular complexes, depending on the cellular context, thereby preserving genomic stability (reviewed in 45 ). In fact, our proteomic analysis also identified ERCC6L as one of the top constitutive interactors of C1orf112, which may likely reflect a role during mitotic progression 18 .…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Alike other scaffolding proteins such as REV7, it is possible that C1orf112 forms different molecular complexes, depending on the cellular context, thereby preserving genomic stability (reviewed in 45 ). In fact, our proteomic analysis also identified ERCC6L as one of the top constitutive interactors of C1orf112, which may likely reflect a role during mitotic progression 18 .…”
Section: Discussionmentioning
confidence: 67%
“…According to this network, we found that C1orf112 behaves similarly to factors of the cellular response to ICL agent in BL cell lines. Previous reports identified C1orf112 (aka Apolo1) as a modulator of chromosome segregation through the regulation of PLK1 activity 18 . As no other genes associated with mitosis progression were enriched in our screens, we reasoned that a different function of C1orf112 may be important for the cellular response to ICL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that regulation of RAD51 dynamics alone may not fully account for the observed synthetic lethality between C1orf112 and ERCC6L , and we cannot rule out that C1orf112 has functions beyond FIGNL1 stabilisation and RAD51 filament formation. Indeed, an additional role for C1orf112 in regulating PLK1 activity during early mitosis has been described recently (Xu et al, 2021). In fact, we identified PLK1 as a potential interactor of C1orf112 in our mitotic mass spectrometry data set (Suppl.…”
Section: Discussionmentioning
confidence: 97%
“…To execute its multiple roles, Cdk1 must phosphorylate its numerous substrates in a spatiotemporally controlled manner. Kinases adopt different mechanisms, such as the structure of the kinase catalytic cleft, the kinase docking site, localization of the kinase, and system‐level competition between substrates, to phosphorylate their substrates selectively (Ubersax & Ferrell, 2007; Xu et al , 2021). Cyclin B determines Cdk1 substrate selectivity through the docking domain and subcellular localization of Cdk1.…”
Section: Discussionmentioning
confidence: 99%